Analisis Kritis Terhadap Kinerja Sektor Pertanian Subsektor Tanaman Pangan - Dahiri Dahiri (Pusat Kajian Anggaran, 2020)
The performance of the agricultural sector in the food plant subsector is currently experiencing a decline, due to a slowdown in GDP growth and a negative trade position every year. The purpose of this study is to determine the determinants of production and efforts to increase the production of the food plant subsector. The research method used exploratory and descriptive methods. The results showed that the determinants of production were influenced by land area and productivity, there was a change in the function of agricultural land, and alsintan in post-harvest was still relatively minimal. Efforts to overcome these problems are that the government must absorb the production of farmers and the provision of agricultural machine tools (alsintan) must be complete, namely preharvest and post-harvest.